Transition properties of X2Σ+, A2Π, B2Σ+, C2Π, a4Σ+, and b4Δ states of boron monosulfide. (September 2021) - Sun, Shan; Shi, Deheng
Highlights: Lifetime is 9 – 20 and 12 – 22 μs for the A 2 Π1/2 and A 2 Π3/2 states, respectively. B 2 Σ + 1/2 –A 2 Π3/2, B 2 Σ + 1/2 –A 2 Π1/2 and C 2 Π3/2 –A 2 Π1/2 transitions are strong. C 2 Π3/2 – X 2 Σ + 1/2, C 2 Π1/2 – X 2 Σ + 1/2 and C 2 Π1/2 –A 2 Π3/2 transitions are the strongest. b 4 Δ1/2 –X 2 Σ + 1/2, b 4 Δ1/2 –A 2 Π3/2 and b 4 Δ1/2 –A 2 Π1/2 forbidden transitions are the strongest. Lifetimes are 361 – 553 and 298 – 513 ns for the C 2 Π1/2 and C 2 Π3/2 states, respectively. Abstract: A number of experiments have been performed to measure the transition properties of the low–lying states of boron monosulfide; however, only a few theoretical results have been reported in the literature. Thus, the transition properties of several of the lowest–lying states are investigated herein. The potential energy curves of the Ω states generated from the X 2 Σ +, A 2 Π, B 2 Σ +, C 2 Π, a 4 Σ +, and b 4 Δ states and the transition dipole moments between them were calculated using icMRCI approach. The radiative lifetimes of the first 16 levels were of the order of 9 – 20, 12 – 22, and 1.3 – 6.5 μs for the A 2 Π1/2, A 2 Π3/2, and B 2 Σ + 1/2 states, respectively; those were approximately 361 – 553 and 298 – 513 ns for the C 2 Π1/2 and C 2 Π3/2 states, respectively. The C 2 Π3/2 – X 2 Σ + 1/2, C 2 Π1/2 – X 2 Σ + 1/2, and C 2 Π1/2 – A 2 Π3/2 transitions were the strongest, followed by the B 2 Σ + 1/2 – A 2 Π3/2, B 2 Σ + 1/2 – A 2 Π1/2, and C 2 Π3/2 – A 2 Π1/2 transitions. The transitions from the a 4 Σ + and b 4 Δ states to the X 2 Σ + state were evaluated. The radiative lifetimes of the first 16 levels were of the order of 3.2 – 6.0, 8.9 – 17.3, and 61 – 7644 ms for the a 4 Σ + 3/2, a 4 Σ + 1/2, and b 4 Δ5/2, respectively; those were approximately 15 – 1430 and 7 – 1006 μs for the b 4 Δ3/2 and b 4 Δ1/2 states, respectively. Among these forbidden transitions, the emissions from the b 4 Δ1/2 – X 2 Σ + 1/2, b 4 Δ1/2 – A 2 Π3/2, b 4 Δ1/2 – A 2 Π1/2, b 4 Δ1/2 – X 2 Σ + 1/2, b 4 Δ1/2 – A 2 Π3/2, and b 4 Δ1/2 – A 2 Π1/2 systems were strong. The distribution of the radiative lifetime at a level υ versus the rotational quantum number J was evaluated for the A 2 Π1/2, A 2 Π3/2, B 2 Σ + 1/2, C 2 Π1/2, and C 2 Π3/2 states. Graphical abstract: The radiative lifetimes are 9 – 20, 12 – 22, and 1.3 – 6.5 μs for the A 2 Π1/2, A 2 Π3/2, and B 2 Σ + 1/2 states, respectively; those were 361 – 553 and 298 – 513 ns for the C 2 Π1/2 and C 2 Π3/2 states, respectively; these are of the order 3.2 – 6.0, 8.9 – 17.3, and 61 – 7644 ms for the a 4 Σ + 3/2, a 4 Σ + 1/2, and b 4 Δ5/2, respectively; those were 15 – 1430 and 7 – 1006 μs for the b 4 Δ3/2 and b 4 Δ1/2 states, respectively. The C 2 Π3/2 – X 2 Σ + 1/2, C 2 Π1/2 – X 2 Σ + 1/2, and C 2 Π1/2 – A 2 Π3/2 transitions are strongest, followed by the B 2 Σ + 1/2 – A 2 Π3/2, B 2 Σ + 1/2 – A 2 Π1/2, and C 2 Π3/2 – A 2 Π1/2 transitions. The b 4 Δ1/2 – X 2 Σ + 1/2 transition is the strongest, followed by the b 4 Δ1/2 – A 2 Π3/2 and b 4 Δ1/2 – A 2 Π1/2 forbidden transitions. The strong emissions from the A 2 Π3/2 – X 2 Σ + 1/2 and A 2 Π1/2 – X 2 Σ + 1/2 systems are mainly in the visible region; only a small number are in the IR and UV regions. The strong emissions from the B 2 Σ + 1/2 – X 2 Σ + 1/2, C 2 Π1/2 – A 2 Π3/2, C 2 Π1/2 – A 2 Π1/2, C 2 Π3/2 – A 2 Π3/2, and C 2 Π3/2 – A 2 Π1/2 systems are located in the UV and visible region; those from the B 2 Σ + 1/2 – A 2 Π3/2 and B 2 Σ + 1/2 – A 2 Π1/2 transitions are in the visible region; those from the C 2 Π3/2 – X 2 Σ + 1/2 and C 2 Π1/2 – X 2 Σ + 1/2 systems are in the UV region; those from C 2 Π3/2 – B 2 Σ + 1/2 and C 2 Π1/2 – B 2 Σ + 1/2 systems are of IR light. Image, graphical abstract